2018
DOI: 10.1111/scd.12303
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care for patients with developmental disabilities: A survey of Michigan general dentists

Abstract: A majority of Michigan general dentists treat patients with developmental disabilities. Addressing barriers like training and improved reimbursements might help in increasing the number of dentists willing to treat patients with developmental disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Parents with either private or public health insurance policies were more likely to self-report that their children had all their OH needs met. 2c). Perspectives of dentists Byrappagari, Jung & Chen, 2018 (USA) [67]Cross–sectional studyExamine level of access individuals with DD have to dental care and explore the dentists’ practices, attitudes and barriers to providing care to this population.279 dentists (male 75.6%)Most dentists provided care for people with DD (80.3%) and 58% were confident to do so. All dentists identified training and better reimbursement for services as key to improving care for these patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents with either private or public health insurance policies were more likely to self-report that their children had all their OH needs met. 2c). Perspectives of dentists Byrappagari, Jung & Chen, 2018 (USA) [67]Cross–sectional studyExamine level of access individuals with DD have to dental care and explore the dentists’ practices, attitudes and barriers to providing care to this population.279 dentists (male 75.6%)Most dentists provided care for people with DD (80.3%) and 58% were confident to do so. All dentists identified training and better reimbursement for services as key to improving care for these patients.…”
Section: Resultsmentioning
confidence: 99%
“…Byrappagari et al [67] examined the perspectives of dentists ( n = 291) in Michigan, USA of providing care to people with IDD. The results indicated the following barriers: 1) behaviour management problems; 2) inadequate training/experience; 3) severity of patient’s condition; 4) inadequately trained staff; and 5) the additional time required to treat versus inadequate reimbursement.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the groups analyzed in the present study were the following: Two different questionnaires, one for each group, were prepared. The optimization of the detection tools started from the analysis of questionnaires in the literature [13,24], then moving forward with some interviews to ANFFAS operators and family members or caregivers as well as to dentists.…”
Section: Study Design and Sample Selectionmentioning
confidence: 99%
“…Patient anxiety and noncompliance during examinations is a commonly cited barrer to receiving routine dental care (Duker et al, 2017 ; Gabre et al, 1999 ; Morgan et al, 2012 ; Wilson et al, 2019 ; Zhou et al, 2017 ). Research suggests that many individuals with IDD may engage in problem behavior to escape dental examinations (Altabet, 2002 ; Cumella et al, 2000 ; Kupzyk & Allen, 2019 ) and that dentists may exclude individuals with IDD from their practice as a result of these behavioral difficulties (Byrappagari et al, 2018 ; Casamassimo et al, 2004 ; Derbi et al, 2016 ; Duker et al, 2017 ). Some dental professionals also may require the use of restraints, sedation, or anesthesia to treat patients with IDD (Boynes et al, 2010 ; Connick et al, 2000 ; Dougherty, 2009 ).…”
mentioning
confidence: 99%
“…In light of these findings, it is not surprising that dental students and professionals often report feeling unprepared to serve this population (e.g., Byrappagari et al, 2018 ; Dao et al, 2005 ; Wolff et al, 2004 ; see also El-Yousfi et al, 2019 , for a review). For example, in a survey of 562 dental students and professionals, only about 38% reported that their dental education well prepared them to serve this population and only about half reported that they planned to treat or currently treated patients with disabilities (Smith et al, 2006 ).…”
mentioning
confidence: 99%